2016
DOI: 10.3171/2015.6.spine15226
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography parameters for atlantooccipital dislocation in adult patients: the occipital condyle–C1 interval

Abstract: OBJECT Atlantooccipital dislocation (AOD) in adults cannot be diagnosed with adequate specificity and sensitivity using only CT or plain radiography, and the spine literature offers no guidelines. In children, the most sensitive and specific radiographic measurement for the diagnosis of AOD is the CT-based occipital condyle–C1 interval (CCI). The goal of the current study was to identify the normal CCI in healthy adults and compare it with the CCI in adults with AOD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 34 publications
1
19
1
2
Order By: Relevance
“…A revised CCI was done by Gire, Roberto, Bobinski, and Klineberg [ 3 ], and stated that AOD can be accurately diagnosed by a unilateral dislocation or dissociation in the sagittal plane of the C1 joint of 2.5 mm. The revised CCI had a 100% sensitivity, specificity, positive predictive value, and negative predictive value and has been confirmed in other studies [ 2 , 4 ].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A revised CCI was done by Gire, Roberto, Bobinski, and Klineberg [ 3 ], and stated that AOD can be accurately diagnosed by a unilateral dislocation or dissociation in the sagittal plane of the C1 joint of 2.5 mm. The revised CCI had a 100% sensitivity, specificity, positive predictive value, and negative predictive value and has been confirmed in other studies [ 2 , 4 ].…”
Section: Discussionsupporting
confidence: 72%
“…In a study by Campo, Kalb, and Baron [ 4 ], the CCI was proposed to be 1.5 mm as the upper limit of the normal values with a 100% sensitivity and specificity. Other studies report 2.5 mm as the cut off [ 2 - 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These principles are also relevant in adults. Recently, Martinez-del-Campo et al 8 found a CCI cutoff of 1.5 mm using a similar method of comparison in a cohort of 81 adult patients-59 without AOD and 22 with AOD.…”
Section: Screening For Aodmentioning
confidence: 99%
“…An MRI is recommended to assess the integrity of the craniocervical ligaments for determining the stability of OCF (level III recommendation). 6 The small amount of cases explains the variety of different treatment recommendations, ranging from conservative therapy with neck immobilization to surgical fusion (level III evidence). 7 In a retrospective study (n = 23), Byström et al, 8 using the Mueller classification, found no unstable patients.…”
Section: Occipital Condyle Fractures: Classification and Managementmentioning
confidence: 99%